Tunable structural and magnetic properties of chemically synthesized dual-phase Co2NiGa nanoparticles - Wang, Changhai; Levin, Aleksandr A.; Fabbrici, Simone; Nasi, Lucia; Karel, Julie; Qian, Jinfeng; Barbosa, Carlos E. Viol; Ouardi, Siham; Albertini, Franca; Schnelle, Walter; Borrmann, Horst; Fecher, Gerhard H.; et al. (Journal of Materials Chemistry C, 2016)
We report the structural and magnetic properties of chemically synthesized dual-phase Co2NiGa shape memory Heusler nanoparticles (NPs). Rietveld analysis of the X-ray diffraction (XRD) data reveals a dual-phase structure for all studied Co2NiGa NPs: the B2 ordered cubic austenite (β) and the tetragonal (γ or martensite β′) phases. We find that the fraction of the tetragonal γ-phase and magnetic properties of NPs consisting of β + γ phases prepared using a heating rate of 0.5 K min-1 can be tuned by varying the Ni-content. Higher saturation magnetization and Curie temperature are observed for Co2NiGa NPs with a higher fraction of the γ-phase. Dual-phase β + γ Co2NiGa NPs exhibit the highest Curie temperature (1153 K) of all known Heusler NPs. Furthermore, the martensite β′-phase is found to coexist with the β-phase for NPs synthesized using a higher heating rate of 2 K min-1. Co2NiGa NPs of mixed β + β′ phase are paramagnetic at room temperature and exhibit low magnetization due to the presence of the martensite phase. High temperature XRD measurements of Co2NiGa NPs with β + β′ phases confirm their irreversible phase transition of the β-phase starting at a temperature of 837 K and the structural stability of the tetragonal β′-phase. The developed new synthetic method makes it possible to fabricate Co2NiGa NPs with structure and properties tailored for high temperature magnetic shape memory devices at the nanoscale.
CRIS-Team Scopus Importer:2023-03-20